2022
DOI: 10.52547/rbmb.10.4.664
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between IL-2, IL-17 Concentrations, and Serum Creatinine Levels in Men with Chronic Kidney Diseases

Abstract: Background: Chronic kidney disease (CKD), is a major public health challenge worldwide. It is more prevalent in developed countries compared with the rest of the world, due to the higher rates of life expectancy and unhealthy lifestyle related factors. This aim of the current study is to evaluate the relationship between interleukins IL-2 and IL-17 concentrations and kidney function markers in men with CKD. Methods: Forty-five men with CKD and seventy controls were enrolled in the current study to assess the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
(90 reference statements)
0
14
0
Order By: Relevance
“…Nitrogen is essential in plant growth at all stages, as it is known that the flowering stage requires a low level of nitrogen and a high level of phosphor. However, several kinds of literature indicated that sufficient or high level of nitrogen application caused an increase in plant flowering due to the activation of gene expression involved in the flowering process [34][35][36] that explain the increase of inflorescences and flowers number after foliar application of A. maurorum extracts (Figures 5 and 6). Results also show a significant increase in the number of seeds after foliar spray with shoot and root extracts of A. maurorum compared to control except the spraying with 1.5 gL -1 of shoot extract (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen is essential in plant growth at all stages, as it is known that the flowering stage requires a low level of nitrogen and a high level of phosphor. However, several kinds of literature indicated that sufficient or high level of nitrogen application caused an increase in plant flowering due to the activation of gene expression involved in the flowering process [34][35][36] that explain the increase of inflorescences and flowers number after foliar application of A. maurorum extracts (Figures 5 and 6). Results also show a significant increase in the number of seeds after foliar spray with shoot and root extracts of A. maurorum compared to control except the spraying with 1.5 gL -1 of shoot extract (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…In table 5, ROC curve checking offered that the best biomarkers were fit to distinguish patients with hyperthyroidism patients from HCs T3 and T4 [AUS= 1; P<0.0001; Cut-off value: (> 2.22, > 106.9) ; Sen%: 100 and Spec%: 100] respectively, also neudesin was established to be a better predicator for hyperthyroidism [AUC =0.9043; P = <0.0001; Cut-off value: < 5.87; Sen%: 82.14; Spec%: 82. 14 Thyroid dysfunction can manifest as low hyperthyroidism or high hypothyroidism, respectively, with raised or lowered serum TSH levels that affect the synthesis of the thyroid hormones T3 and/or T4, respectively. The most frequent causes of thyroid dysfunction in places with abundant iodine are autoimmune diseases like Graves' disease and Hashimoto's thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…However, hyperthyroidism may cause abnormally low cholesterol levels or an improvement in lipid profile for no apparent reason [12]. Many Iraqi studies have examined the relationship between inflammatory variables and various diseases [13,14], but this study is the first to study the relationship of neudesin to thyroid dysfunction.…”
Section: Introductionmentioning
confidence: 96%
“…The qualitative characteristics of the fruits were measured, where proportion of dry mass and water content (%), the proportion of total soluble solids (T.S.S.) (%), which were measured using Hand Refractometer according to 16 , total and reducing sugars and sucrose (%) which were estimated using The Lane and Eynon method mentioned by 17 , the total neutralizable acidity (%) determined as in 18 and the proportion of tannins (%) calculated by the method of 19 .…”
Section: Methodsmentioning
confidence: 99%